Study of Challenging Calcium Alkoxides in Solution by Electrospray Ionization Mass Spectrometry (Part 1). Issue 4 (August 2013) - Peruzzo, Valentina; Chiurato, Matteo Andrea; Tomasin, Patrizia; Traldi, Pietro; Favaro, Monica
Electrospray ionization was applied on calcium alkoxides studying the most suitable operative conditions for their detection/identification. To reach this aim, calcium methoxide and ethylate were obtained by two different synthetic pathways, in order to understand their possible different aggregation states. The reaction mixture shows the presence of a supernatant and of a precipitate poorly soluble in most organic solvents. The purpose of this preliminary study is to understand the qualitative differences between the precipitated species and the ones in solution by analyzing both of them with the same analytical method. The electrospray ionization (ESI) operating conditions (voltages, temperatures, solvents) allow not only the detection of single species but also the study of clusters present in solution. Particular attention was paid to establishing the role of ESI conditions in the formation of the detected species. Experiments performed at different sprayer voltages (1 kV, 2 kV, 3 kV and 4 kV) proved that ESI does not perturbate the equilibria present in the original solution, demonstrating that the technique can be a useful tool to achieve information on this class of compounds.